Anticipation of digital patterns. (30th June 2017) - Ochs, Karlheinz; Ziegler, Martin; Hernandez‐Guevara, Eloy; Solan, Enver; Ignatov, Marina; Hansen, Mirko; Gill, Mahal Singh; Kohlstedt, Hermann
Summary: A memristive device is a novel passive device, which is essentially a resistor with memory. This device can be used for novel technical applications like neuromorphic computation. In this paper, we focus on anticipation—a capability of a system to decide how to react in an environment by predicting future states. Especially, we have designed an elementary memristive circuit for the anticipation of digital patterns, where this circuit is based on the capability of an amoeba to anticipate periodically occurring unipolar pulses. The resulting circuit has been verified by digital simulations and has been realized in hardware as well. For the practical realization, we have used an Ag‐doped TiO2− x ‐based memristive device, which has been fabricated in planar capacitor structures on a silicon wafer. The functionality of the circuit is shown by simulations and measurements. Finally, the anticipation of information is demonstrated by using images, where the robustness of this anticipatory circuit against noise and faulty intermediate information is visualized. Abstract : Anticipation is the capability of a system to decide how to react in an environment by predicting future states. Here, we have designed a memristive circuit for the anticipation of digital patterns. The resulting circuit has been verified by digital simulations and has also been realized in hardware. The functionality of the circuit is the anticipation of information, which is demonstrated by using images, where the robustness of this anticipatory circuit against noise and faulty intermediate information is visualized.